PENGARUH PENGERINGAN MENGGUNAKAN ROOM DRYER TERHADAP KUALITAS TEPUNG SAGU - Sudirman, Nurafni Apriani; Sukainah, Andi; Yanto, Subari (Jurnal Pendidikan Teknologi Pertanian, 2018)
The purpose of this research is to know the effect of drying using room dryer to the quality of sago flour. This research is an experiment research with Factorial Complete Random Design consisting of two factors, namely: drying type (traditional drying andÂ  room drying) and material thickness treatment (1cm, 2cm and 3cm). The test parameters observed were moisture content, starch content, amylose content, amylopectin content and color test. The analytical technique used in this study is the of analysis of variety using SPSS version 23. The results showed that the best treatment is room drying and 1 cm thickness, water content (10.44%), starch content (53.73%), amylose content (2.27%), amylopectin content (52.42%), color (90.74%) sago resulting.